Intersections of Culture and Language in Students’ Writing: An Analytical Reflection on Style and Self-Perception - Sri Widyarti Ali (Jurnal Riksa Cendikia Nusantara, 2026)
This study explores the intersection of culture, language, and identity in the academic writing of EFL students at Universitas Negeri Gorontalo. Employing a case study design, it analyzes narrative essays and questionnaire responses from twelve second-semester students to investigate how cultural backgrounds influence rhetorical style and how students perceive their writing identities. The findings reveal that students often incorporate traditional storytelling, communal perspectives, and religious or emotional expressions in their writing, reflecting deeply rooted cultural values. Despite facing challenges such as linguistic interference, limited vocabulary, and unfamiliarity with academic conventions, students creatively negotiate meaning by blending local and academic discourses. However, many express uncertainty about integrating their cultural voices due to institutional norms that prioritize standard English. This study underscores the importance of culturally responsive pedagogy in fostering inclusive writing practices that honor students’ multilingual and multicultural identities.